Digital literacy and cybersecurity in higher education: the unseen power of academic librarians - Baharuddin, Mohammad Fazli; Jalil, Abdurrahman; Mohd Amin, Zahari; Rahmad, Fadhilnor; Mohamed Shuhidan, Shamila (International Journal of Evaluation and Research in Education (IJERE), 2025)
The increasing reliance on digital technologies in higher education has amplified the need for students to develop digital literacy and cybersecurity awareness. However, many undergraduate students lack the competencies required for responsible and secure digital engagement, posing significant risks in the digital landscape. Academic librarians, as key facilitators of information literacy, are uniquely positioned to address these challenges, yet their roles in promoting digital literacy and cybersecurity awareness remain underexplored. The study addresses the following key issues: how do academic librarians play their roles on undergraduate students’ digital literacy and cyber security awareness; what are the challenges related to library initiatives; and, perhaps most importantly, what are the strategies do librarians employ to improve it? Using a qualitative research methodology, data were collected through interviews with six academic librarians and analyzed using thematic analysis. The findings reveal that academic librarians play critical roles in fostering digital literacy and cybersecurity by teaching information literacy, promoting ethical online behavior, and enhancing students’ digital safety practices. Challenges identified include limited resources, diverse digital skill levels among students, and difficulties in maintaining student engagement. Librarians address these issues through strategies such as faculty collaboration, integrating digital literacy programs, employing interactive learning tools, and pursuing continuous professional development. This research offers actionable insights for integrating digital literacy and cybersecurity initiatives into library services, improving librarian training, and enhancing the sustainability and visibility of academic libraries within higher education institutions.